2022
DOI: 10.51923/repae.v7i3.257
|View full text |Cite
|
Sign up to set email alerts
|

A Volatilidade No Setor De Transporte Aéreo: Evidências Da Sua Ocorrência, Causas E Estratégias Para Enfrentá-La

Abstract: Desde o seu surgimento, o setor de transporte aéreo foi protagonista na transformação do mundo moderno, atuando como catalisador dos negócios e do turismo. No entanto, o seu ambiente tem sido caracterizado como volátil porque as companhias aéreas operam em um padrão cíclico de altos e baixos. Por meio de uma extensa revisão de literatura e uma detalhada análise documental que envolveu as principais companhias aéreas e fabricantes de aviões do mundo, os autores buscaram evidências da volatilidade no setor, iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…A fuzzy cognitive map of 39 concepts to analyse the links between them and estimate the causes and effects of volatility is drawn in [1]. Guerra et al conducted a literature review of volatility in air transport, identified factors that influence it and suggested strategies for addressing it [33]. However, they do not mention volatility as a measure of flight fluctuation.…”
Section: State Of the Artmentioning
confidence: 99%
“…A fuzzy cognitive map of 39 concepts to analyse the links between them and estimate the causes and effects of volatility is drawn in [1]. Guerra et al conducted a literature review of volatility in air transport, identified factors that influence it and suggested strategies for addressing it [33]. However, they do not mention volatility as a measure of flight fluctuation.…”
Section: State Of the Artmentioning
confidence: 99%